2015
DOI: 10.1016/j.addbeh.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Depression and nicotine dependence from adolescence to young adulthood

Abstract: Introduction Despite the highly replicated relationship between depression and nicotine dependence, little is known about this association across both time and levels of lifetime smoking exposure. In the present study, we evaluate if symptoms of depression are associated with emerging nicotine dependence after accounting for smoking exposure and whether this relationship varies from adolescence to young adulthood and across increasing levels of smoking. Patients and Methods The sample was drawn from the Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
(25 reference statements)
4
33
0
Order By: Relevance
“…Depressive symptoms were associated with fewer negative cigarette effects, which may account for high comorbidity between depression and tobacco dependence (Dierker, et al, 2015). At first glance this may seem to contrast with the finding that depressive symptoms were associated with more negative cannabis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms were associated with fewer negative cigarette effects, which may account for high comorbidity between depression and tobacco dependence (Dierker, et al, 2015). At first glance this may seem to contrast with the finding that depressive symptoms were associated with more negative cannabis effects.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of homomeric α7 receptors or heteromeric nAChRs containing the β2 subunit in the amygdala mimics the effects of antidepressants (Mineur et al, 2015). Moreover, depressive symptoms and nicotine dependence are strongly associated across age and duration of lifetime smoking exposure (Dierker et al, 2015). It is still not clear however whether the association between MDD and nicotine-dependence results from one causing the other, or from shared neurobiological circuitry.…”
Section: Role Of Polyamines In Stress Response and Depressionmentioning
confidence: 99%
“…Conversely, among individuals with lifetime MDD, 30% have nicotine dependence, 21% have alcohol dependence, and 6% have other drug dependence (Hasin et al, 2005). The comorbidity with depression has been found to be robust across substances, with the link between smoking and depression being particularly well-documented (Dierker et al, 2015; Kassel et al, 2003). The smoking – depression association holds for various classifications of smokers (e.g., ever, regular, and heavy smokers; Husky et al, 2008; Payne et al, 2013) as well as various stages of the smoking trajectory (Audrain-McGovern et al, 2011; Dierker and Donny, 2008; McKenzie et al, 2010; Leventhal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Poulin et al (2005) found that the association between heavy episodic drinking (HED) and depression varied by age for females but not males. A recent study regarding nicotine dependence and depression found that this association was constant across adolescence and young adulthood (Dierker et al, 2015). …”
Section: Introductionmentioning
confidence: 99%